Acetilação do exopolissacarídeo (1→6)-β-D-glucana (lasiodiplodana): derivatização química e caracterização - Sánchez Luna, William Norbey (2016)
Lasiodiplodan is an exocellular β-glucan with biological functionalities such as antioxidant, antiproliferative, hypocholesterolemic, protective activity against DNA damage induced by doxorubicin and hypoglycemic activity. Chemical derivatization of polysaccharide macromolecules has been considered as a potentiating mechanism for bioactivity. In this context, this work proposes the derivatization of lasiodiplodan by acetylation. Acetic anhydride was used as derivatizing agent and pyridine as catalyst and reaction medium. The derivatives obtained were evaluated by its water solubility, degree of substitution (DS), antioxidant potential, and characterized by infrared spectroscopy (FT-IR), thermal analysis, differential scanning calorimetry, X-ray diffraction and scanning electron microscopy. Acetylated derivatives with different degrees of substitution (1.26; 1.03; 0.66 and 0.48) were obtained, and there was correlation between the concentration of derivatizing agent and DS. FT-IR spectroscopy analysis confirmed the insertion of acetyl groups into derivatized macromolecules (LAS-AC) through of specific bands concerning to carbonyl group (C = O) and increase in C-O vibration. SEM analysis indicated that native lasiodiplodan presents morphological structure in the form of thin films with translucent appearance and folds along its length. Derivatization led to morphological changes in the polymer, including aspects thickness, translucency and agglomeration. Thermal analysis indicated the native sample and derivative with DS 0.48 presented three weight loss stages. The first stage occurred until 125 ° C (loss of water) and there were two consecutive events of weight loss (200 ° C - 400 ° C) attributed to molecule degradation. Samples with DS 1.26; 1.03 and 0.66 demonstrated four weight loss stages. The first stage occurred until 130 ° C (loss of water), following by two consecutive events of weight loss (200 ° C - 392 ° C) attributed to degradation of the biopolymer. The fourth stage was between 381 ° C and 532 ° C (final decomposition) with exothermic peaks between 472 ° C and 491 ° C. X-ray diffraction patterns showed that native and acetylated lasiodiplodan have amorphous structure with semicrystalline regions. Derivatization did not contribute to increased solubility of the macromolecule, but potentiated its antioxidant capacity. Acetylation of lasiodiplodan allowed to obtaining a new macromolecule with higher antioxidant potential than the native molecule and with technological properties applicable in various industrial sectors.